School Management Styles Roles in Empowering New Teachers and Practice their Professional Roles in the Directorate of Education for the First Zarqa - Abu Qalbain, Somaya Shaban (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the relationship between the school management styles and the empowering of new teachers and their professional roles from the perspective of teachers in the light of some variables. The study sample consisted of (267) teachers. The results showed the median level in the school management styles and the teachers empowering, professional roles, and there were statistically significant differences in the degree of teachers’ empowering due to the gender in favor of males, and the educational stage teachers of the first three grades. The results indicated that there were no statistically significant differences according to the gender in the professional roles. There were statistically significant differences in the role of the type of school in favor of the mixed and the educational stage teachers of the first three grades. The results showed a statistically significant positive relationship between the democratic style and the teachers empowering and professional roles, and a statistically significant negative relation between the autocratic and the ascetic styles, and the teachers empowering and professional roles.